HEROISM IN JACK LONDON'S THE CALL OF THE WILD - Kalalo-pakasi, Ester Kalalo; Tuna, Jim Ronny; Maukar, Merlin M (SoCul: International Journal of Research in Social Cultural Issues, 2023)
The purpose of this study is to examine the values of heroism in the novel The Call of The Wild by Jack London. This study aims to describe the heroism values contained in the novel The Call of the Wild by Jack London with a objective approach. To analyze the data, the researcher used qualitative methods, because the data were collected in the form of words. Data were collected from primary and secondary sources. The main source is the novel itself entitled The Call of the Wild. Secondary sources are books, articles, internet, and other literary works. In this research, there are six elements of the values of heroism they are: 1) Strength, 2) Bravery, 3) Integrity, 4) Saving Others, 5) Willing to Sacrifice, and 6) Selfless.